2016
DOI: 10.1177/1525740116660817
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Linguistic Awareness Intervention for At-Risk Kindergarteners

Abstract: This study investigated the feasibility of multicomponent linguistic awareness intervention on early literacy skills in at-risk kindergarteners. Seventeen students, including native Spanish-speaking English language learners (n = 10) and native English speakers (n = 7), participated in a 6-week small-group therapy program, for a total of 12 intervention hours. Students received therapy in one of the following: phonological awareness and letter knowledge; morphological awareness; or a three-pronged intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In previous reviews, Bowers et al (2010) and Goodwin and Ahn (2013) found evidence of larger effects for younger learners. This finding was not replicated in our analysis, and in fact, there were only three eligible study reports assessing the effectiveness of morphology instruction in beginning readers (up to two years of formal schooling completed; Apel & Diehm, 2014;Filippini et al, 2012;Zoski & Erickson, 2017)…”
Section: Child Factorsmentioning
confidence: 75%
“…In previous reviews, Bowers et al (2010) and Goodwin and Ahn (2013) found evidence of larger effects for younger learners. This finding was not replicated in our analysis, and in fact, there were only three eligible study reports assessing the effectiveness of morphology instruction in beginning readers (up to two years of formal schooling completed; Apel & Diehm, 2014;Filippini et al, 2012;Zoski & Erickson, 2017)…”
Section: Child Factorsmentioning
confidence: 75%
“…The intervention described in this teaching tip helped a group of at‐risk kindergarten students, including English learners, to make large gains in their MA, word reading, and spelling after a total of 12 hours of intervention (four days a week for six weeks; Zoski & Erickson, ). Teachers could repeat this instructional sequence with the books suggested in Table or incorporate some of these ideas into parts of their existing literacy intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, efforts to target MA can improve reading, MA, and PA outcomes for kindergarten students who are at risk for developing later reading disabilities (Apel, Brimo, Diehm, & Apel, ; Zoski & Erickson, ). MA instruction also supports older students with identified reading disabilities (Wolter & Dilworth, ) and students who are English learners (Filippini, Gerber, & Leafstedt, ).…”
Section: Early Developing Suffixes In Oral Languagementioning
confidence: 99%
See 1 more Smart Citation
“…Note. E = experimental, QS = quasi-experimental, SA = stand-alone, P = part of comprehensive instruction, T = teacher, R = researcher, UC = usual classroom, AT = alternative treatment, NA = not available Our analysis suggested that there were six major trends: (a) most of the studies focused on older children in Grade 3 or above; only two studies included young children in kindergarten or Grade 1 (Filippini, 2007;Zoski & Erickson, 2017); also, the majority of research was based on Spanish-speaking L2 English learners in the US; (b) there were more quasi-experimental studies than experimental studies with treatment randomization; (c) eight out of 12 studies implemented morphological instruction as part of a more comprehensive curriculum rather than providing it as a stand-alone treatment; (d) the majority of primary studies reported fidelity and feasibility of morphological instruction; (e) there was great variation in the length of instructional time, ranging from one 45-minute session in total (Zhang et al, 2010) to 72 sessions totaling 3,780 minutes (Kieffer & Lesaux, 2012); and (f) there was no notable trend with regard to the following three features. First, in terms of learners' language backgrounds in the treatment group, half of previous research studies included L2 English learners only, and the other half mixed L2 and L1 English learners.…”
Section: The Implementation Of Morphological Instruction In the Primary Studiesmentioning
confidence: 99%